THE APPLICATION OF SKOPOS THEORY IN THE SONG LYRICS “HINGGA AKHIR WAKTU” TRANSLATED BY CHRISTIAN BAUTISTA - Jati Widya Iswara (SALEE: Study of Applied Linguistics and English Education, 2020)
The aims of this study were to analyze how many translation strategies found as applied in translating process of song lyrics entitled Hingga Akhir Waktu translated into English version by Chirstian Bautista as a singer and also the translator. The data were analyzed by Rainer Schulte and John Biuret’s translation strategies. Since the data consists of words and sentences, qualitative descriptive was applied in this research. The result of the study showed that there were certain types of translation strategies found in the process of translating song lyrics. The findings showed that the rules of Skopos theory in the translating process were running well. Keywords: Skopos Theory; Translation Strategies; Song Lyrics; Hingga Akhir Waktu